2018
DOI: 10.3892/etm.2018.6418
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of mycophenolate mofetil for IgA nephropathy: An updated meta‑analysis of randomized controlled trials

Abstract: The efficacy and safety of mycophenolate mofetil (MMF) for immunoglobulin A nephropathy (IgAN) remains debatable. Therefore, the present meta-analysis was conducted with randomized controlled trials (RCTs). PubMed/MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials were analyzed to identify eligible trials. The pooled risk ratio (RR) with 95% confidence interval (CI) was estimated for all the dichotomous outcome measures. A total of eight RCTs with nine publications (n=510 patients) were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(40 reference statements)
0
5
0
1
Order By: Relevance
“…Not long ago, scholars reported that corticosteroids + MMF is an effective treatment in IgAN patients with a sustained decline in kidney function accompanied by persistent proteinuria and haematuria despite optimized conservative treatment ( Huerta et al, 2022 ). However, foreign prospective studies have not found that MMF has a renoprotective effect on IgAN ( Zheng et al, 2018 ). The inconsistency in research results in China and abroad suggests that genetic heterogeneity of different races has an impact on the pathogenesis of IgA.…”
Section: Discussionmentioning
confidence: 99%
“…Not long ago, scholars reported that corticosteroids + MMF is an effective treatment in IgAN patients with a sustained decline in kidney function accompanied by persistent proteinuria and haematuria despite optimized conservative treatment ( Huerta et al, 2022 ). However, foreign prospective studies have not found that MMF has a renoprotective effect on IgAN ( Zheng et al, 2018 ). The inconsistency in research results in China and abroad suggests that genetic heterogeneity of different races has an impact on the pathogenesis of IgA.…”
Section: Discussionmentioning
confidence: 99%
“…Turning our attention to mycophenolic acid (MPA) derivatives, most of the evidence of its efficacy in IgAN is limited to native kidneys rather than recurrent disease. A metaanalysis looking at eight randomized clinical trials involving 510 patients found no overall differences in rates of disease remission or development of ESKD among regimens that did or did not include mycophenolate mofetil (MMF) [70]. On a sub-analysis, MMF improved renal remission (complete or partial) compared to placebo (three trials, relative risk 2.15; p = 0.010) but compared to those on an immunosuppressive regimen without MMF there were no differences (four trials, relative risk 1.14, p = 0.146).…”
Section: Treatmentmentioning
confidence: 99%
“…Small trials with Mycophenolate mofetil and hydroxychloroquine revealed mixed results in Asian groups [ 136 , 137 ]. A meta-analysis of RCTs for treatment with the mycophenolate mofetil in IgA showed no additional benefit or adverse events than other immunosuppressants [ 138 ]. Even rituximab, a monoclonal antibody against CD20+ B cells, does not improve proteinuria and renal function [ 139 ].…”
Section: Iga Nephropathymentioning
confidence: 99%